WORK DEMAND PATTERN ANALYSIS FOR MGNREGA: WITH SPECIAL REFERENCE TO 18 INDIAN STATES - Shriram KADIYA; Sapna PARASHAR; Sanket VATAVWALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
MGNREGA (Mahatma Gandhi National Rural Employment Guarantee Act) is Indian government’s flagship social safety net program. World Bank in year 2015 announced MGNREGA as world’s largest public employment guarantee program. According to an India Today (February, 2016) report, around 200 million people were provided with work under MGNREGA. The present study focuses upon 18 select Indian states’ work demand pattern under MGNREGA. Each state chosen under study has a specific geographic location, weather pattern, economy and population. Month wise data (secondary in nature) of work demand (in terms of number of persons) for years 2012-13, 2013-14, 2014-15 and 2015-16 for all the selected 18 states have been considered for the analysis. The research hypothesis states that there were no differences between four years’ work demand pattern for each state. The result varied significantly: twelve states had no significant differences between four years’ work demand pattern, while six states had significant differences between four years’ work demand pattern. The research outcome explains that every state has a unique work demand pattern and the work demand pattern varies depending upon factors such as weather system of the state, other available employment opportunities, poor implementation at Panchayat (village governing body) level and low awareness amongst rural people. The research outcome could help government to understand the varying nature of work demand in each state in each month. The research revelations could also assist government to improve its promotion and implementation policies to promote MGNREGA differently in those states facing work demand inconsistencies.